2017
DOI: 10.1074/jbc.m117.777235
|View full text |Cite
|
Sign up to set email alerts
|

Hendra virus fusion protein transmembrane domain contributes to pre-fusion protein stability

Abstract: Edited by Charles E. SamuelEnveloped viruses utilize fusion (F) proteins studding the surface of the virus to facilitate membrane fusion with a target cell membrane. Fusion of the viral envelope with a cellular membrane is required for release of viral genomic material, so the virus can ultimately reproduce and spread. To drive fusion, the F protein undergoes an irreversible conformational change, transitioning from a metastable pre-fusion conformation to a more thermodynamically stable post-fusion structure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 54 publications
5
21
0
Order By: Relevance
“…Viral fusion proteins drive the fusion of viral and cellular membranes, a key early step in the entry of enveloped viruses. We have previously shown that the TM domains of several paramyxovirus fusion proteins associate in isolation and that disruption of TM-TM association by mutagenesis of a key L/I zipper motif resulted in a HeV F protein that triggered prematurely (11,18). Based on the previous studies, we examined the ability of paramyxovirus TM-TM interactions to be targeted with exogenous proteins containing the TM domain to cause disruption in overall protein structure and function (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Viral fusion proteins drive the fusion of viral and cellular membranes, a key early step in the entry of enveloped viruses. We have previously shown that the TM domains of several paramyxovirus fusion proteins associate in isolation and that disruption of TM-TM association by mutagenesis of a key L/I zipper motif resulted in a HeV F protein that triggered prematurely (11,18). Based on the previous studies, we examined the ability of paramyxovirus TM-TM interactions to be targeted with exogenous proteins containing the TM domain to cause disruption in overall protein structure and function (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate fusion, the HeV F protein must be at the surface and in its cleaved (F 1 ϩF 2 ) form. Previous work has shown that disruption of the HeV TM interactions significantly lowered the amount of F protein expressed at the cell surface (18). To determine whether the F protein was trafficked to the cell surface in the presence of the exogenous TM proteins, the proteins were analyzed with a radiolabel surface biotinylation assay.…”
Section: Hev F Tm Proteins Interact With the Full-length Hev Fmentioning
confidence: 99%
See 2 more Smart Citations
“…The TM domain was subsequently shown to stabilize the F protein in its pre-fusion conformation [134]. A heptad repeat pattern of β-branched residues (e.g., leucine, isoleucine, threonine, valine) was identified to be highly conserved in the TM domains of 140 PMVs.…”
Section: Novel Functions Of the Pmv-f Transmembrane Domainmentioning
confidence: 99%